Bakti Kepada Orang Tua Sebagai Jalan Menuju Kedewasaan Diri: Refleksi Teologis Amsal 1:8-19 - Thomas Onggo Sumaryanto (Vox Dei: Jurnal Teologi dan Pastoral, 2021)
This paper is an interpretation of Proverbs 1:8-19. The problem to be answered is how to explain theologically and logically that filial piety to parents contains values that become the path to self-maturity according to Proverbs 1:8-19. The method used is literary analysis, dividing Proverbs 1:8-19 into 2 major parts, namely advice to listen to parents (8-9) and warnings to stay away from sinners (10-19). The findings of the study indicate that it is most likely that the teachings of parents are deliberately emphasized in the Proverbs section as a basis for resisting the persuasion or deception of sinners and it is a form of devotion to parents. Theological reflection of Proverbs 1:8-19 generally shows that devotion to parents brings young people to maturity, and especially for Christians, shapes young people into mature people in God.